Metabolic dysregulation and decreased capillarization in skeletal muscles of male adolescent offspring rats exposed to gestational intermittent hypoxia - Wongkitikamjorn, Wirongrong; Wada, Eiji; Hosomichi, Jun; Maeda, Hideyuki; Satrawaha, Sirichom; Hong, Haixin; Yoshida, Ken-ichi; Ono, Takashi; Hayashi, Yukiko K. (Frontiers in Physiology, 2023)
Gestational intermittent hypoxia (IH) is a hallmark of obstructive sleep apnea that occurs frequently during pregnancy, and effects caused by this environmental change during pregnancy may be transmitted to the offspring. In this study, we aimed to clarify the effects of IH in pregnant rats on the skeletal muscle of adolescent offspring rats. Mother rats underwent IH from gestation day 7 to 21, and their 5-week-old male offspring were analyzed. All male offspring rats were born and raised under normoxia conditions. Although no general growth retardation was observed, we found that exposure to gestational IH reduces endurance running capacity of adolescent offspring rats. Both a respiratory muscle (diaphragm; DIA) and a limb muscle (tibialis anterior; TA) showed no histological abnormalities, including fiber size and fiber type distribution. To identify the possible mechanism underlying the reduced running capacity, regulatory factors associated with energy metabolism were analyzed in different parts of skeletal muscles. Compared with rats born under conditions of gestational normoxia, gestational IH offspring rats showed significantly lower expression of genes associated with glucose and lipid metabolism, and lower protein levels of phosphorylated AMPK and AKT. Furthermore, gene expression of adiponectin receptors 1 and 2 was significantly decreased in the DIA and TA muscles. In addition, the DIA muscle from adolescent rats had significantly decreased capillary density as a result of gestational IH. However, these changes were not observed in a sucking muscle (geniohyoid) and a masticating muscle (masseter) of these rats. These results suggest that respiratory and limb muscles are vulnerable to gestational IH, which induces altered energy metabolism with decreased aerobic motor function. These changes were partially owing to the decreased expression of adiponectin receptors and decreased capillary density in adolescent offspring rats.